Diagnóstico de las líneas de emprendimiento de instituciones de educación superior (IES) de Bogotá con características similares a las de la Fundación Universidad de América (2016)
The study aimed to diagnose the lines of entrepreneurship of Higher Education Institutions (HEI) similar to those of the Fundación Universidad América in the city of Bogotá from which, and complemented with studies carried out in different parts of the world, in some cities of Colombia and taking into account the guidelines given by the Law of Entrepreneurship and the Law of Science and Technology, could be proposed a model of entrepreneurship aimed at strengthening the culture of entrepreneurship. For this purpose, a comparison was made between the different HEIs of the city of Bogota in terms of the programs taught, entrepreneurship lines, transversal project, among others. Thus, it was possible to determine the percentage of universities in the city of Bogota that implement within their curriculum, techniques that develop personal competences in terms of entrepreneurship and the impact they have on each of their students and the economic development that this means. To conclude this study, it was sought to construct a written document that would serve as a frame of reference for future research, with a clear analysis of the study of entrepreneurship within HEIs in Colombia.